Significances and meanings of the musical identity of patients and relatives receiving oncological palliative care - Vladimir Araujo de Silva; Neide Aparecida Titonelli Alvim; Sonia Silva Marcon (Universidade Federal de Goias, 2014)
This phenomenological study was structured on Heidegger's theoretical-philosophical framework, with the objective of unveiling the significances and meanings of the musical identity of patients and relatives under oncological palliative care. Individual interviews were performed with 12 clients (seven patients and five relatives) staying at the support residence of the Maringa Female Network Against Cancer. A total of eight musical meetings were performed between January and February of 2011. I understood that the musical identity of the evidenced beings refers to the religious and country music styles, that their significances and meanings are connected to their spirituality and the significant events of their historicity, and that their mood and reflection intermediated by music can influence their musical choice. I gave evidence to the need to consider the music identity and empowerment in musical choices, which carries existential, social, cultural, spiritual and family aspects as qualifying elements of nursing in palliative care. Descriptors: Nursing Care; Oncology Nursing; Music; Music Therapy; Palliative Care.